Book review: Commodification and Content Development in Economics: Ajit Sinha and Alex M. Thomas (Eds.), Pluralistic Economics and Its History. Issue 2 (August 2020) - Scaria, Suma
Ajit Sinha and Alex M. Thomas (Eds.), Pluralistic Economics and Its History . United Kingdom: Routledge, 2019, 298 pp. ISBN: 978-0-367-23235-1.